Investigating ownership structure, company characteristics and online environmental disclosure in Malaysia - Al_arussi, Ali Saleh Ahmed; Al_dhamari, Redhwan Ahmed (OMJP Alpha Publishing, 2017)
This paper focuses on environmental disclosure on the Internet and empirically examines whether ownership structure and company characteristics have a significant association with the level of Internet environmental disclosure (IED) amongst Malaysian companies. Six variables – management ownership, government ownership, firm size, level of technology, industry type, and profitability – have been chosen to be examined in this study. Multiple regression analysis is used to examine these relationships by analysing the data of 201 online annual reports on the websites of Malaysian companies. The results indicate that government ownership, firm size, level of technology and industry type are positively and significantly associated with IED; management ownership is negatively and significantly associated with IED, and profitability did not show a significant relationship. The results of this paper can be used by regulators to enhance and regulate online environmental reports as it is still voluntary based.